Promoting ecological solutions for sustainable infrastructure - Sjolund, Anders (2022)
Sustainable infrastructure needs ecological solutions – it’s time to work together! We, the participants of the IENE 2020 International Conference, acknowledge that: 1. We are facing a significant worldwide expansion of transportation networks; this is especially the case in countries with developing economies. 2. If no action is taken, this global expansion will entail a substantial increase in greenhouse gas emissions, wildlife mortality and landscape fragmentation and change, with devastating effects on climate, biodiversity and ecosystem services. 3. Globally, ecosystem services are estimated to yield more than the Gross World Product of 2019 (https://www.worldometers.info/gdp/). 4. Despite the development and implementation of environmental impact assessment legislation, many existing transportation infrastructure networks are not environmentally friendly. These impacts are far-reaching with a debt being paid daily through unnecessary risks extendable to human health and well-being. 5.The economic, social, and ecological consequences of biodiversity loss and the role of transportation infrastructure is increasingly acknowledged worldwide: •Conservation and restoration of ecological connectivity is a major flagship in the preparation of the upcoming United Nations “Post-2020 Global biodiversity framework” following the recognised failure of the Aichi Targets associated with the loss and fragmentation of natural habitats (Target 5) (https://www.cbd.int/gbo5). •The European Green Deal and the new European Biodiversity Strategy for 2030, adopted by the European Commission in May 2020, stresses the need to develop a resilient Trans-European Nature Network supported by ecological corridors allowing the free flow of genes and individuals (https://ec.europa.eu/info/sites/info/files/communication-annex-eu-biodiversity-strategy-2030_en.pdf). •The Intergovernmental Platform on Biodiversity and Ecosystem Services (IPBES) states that since 1970, transportation infrastructure is an important driver of land use change and associated loss of terrestrial biodiversity (https://ipbes.net/global-assessment). •The World Economic Forum 2020 recognised that biodiversity loss is one of the major threats with ‘plausible higher than average impact’ on Global Economies (https://www.weforum.org/reports/the-global-risks-report-2020). 6.To ahieve sustainability, infrastructure development must be decoupled from its negative effect on biodiversity. This requires immediate, stringent action and shared responsibilities from all stakeholders. 7.Regional, national, and worldwide networks of experts, including researchers, practitioners, landscape designers, and managers, address such concerns through knowledge-sharing platforms that promote effective ecological solutions. 8.The scarcity of collective and coordinated efforts, such as joint decision-making processes involving environmental, transportation, energy, policy and financing agencies, is still a major obstacle to achieve sustainability in transportation infrastructure projects.